The Influence of Top Management Team Heterogeneity on Firms' Competitive Moves - Hambrick, Donald C.; Cho, Theresa Seung; Chen, Ming-Jer (Administrative Science Quarterly, 1996)
Donald C. Hambrick, Theresa Seung Cho, Ming-Jer Chen, The Influence of Top Management Team Heterogeneity on Firms' Competitive Moves, Administrative Science Quarterly, Vol. 41, No. 4 (Dec., 1996), pp. 659-684